EFFORTS TO IMPROVE SMES PERFORMANCE IN PURWOKERTO THROUGH FINANCIAL LITERACY, FINANCIAL INCLUSION AND DIGITATION - EMIR SURYA RAHMAJATI; POPPY DIAN INDIRA KUSUMA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2023)
This study aims to examine the effect of financial literacy, financial inclusion, and digitization on the performance of SMEs. This study is quantitative and uses a survey method to collect data. An online questionnaire was distributed to respondents from SME managers in Purwokerto city. Data were analyzed using multiple regression analysis. The sample in this study was 118 respondents selected using a convenient sampling method. The results show that financial literacy, financial inclusion, and digitization positively affect SMEs’ performance. The results imply the importance of increasing financial literacy, financial inclusion, and digitization among SMEs in Purwokerto. The findings emphasize the crucial role of financial literacy, financial inclusion, and digitization in enhancing the performance and sustainability of SMEs in Purwokerto. These implications can lead to a supportive ecosystem that empowers SMEs, fosters economic growth, and creates regional employment opportunities.